HR Perspectives of Russian Universities: Who Will Teach in the Near Future? - Yu. S. Ezrokh (Образование и наука)
Introduction. A university professor is the major actor of the preparation of future specialists, the carrier of significant amount of implicit knowledge, which due to objective reasons cannot be formalised. For the full functioning of the higher school and its development, it is necessary to form and support the affective system of uninterruptable reproduction of qualified scientific and pedagogical personnel. The growing problem of ageing of higher-education teaching personnel (i.e. faculty) of Russian universities, which is not isolated from other negative trends, causes a threat to the overall human potential of the country.Aim. Within the scope of a further scientific discussion1, the aims of the article are the following: to comprehensively discuss the crisis situation in the field of higher education HR in Russia, to identify the key causes of the crisis and to indicate the possibilities of overcoming it.Methodology and research methods. The methodological framework is based on systematic approach, which includes general scientific methods (deduction, induction, generalisation, comparative analysis, etc.) and special research methods (historical method, correlation and regression analysis, statistical analysis, etc.).Results and scientific novelty. The causes of demographic crisis of the Russian higher education institution are considered: a) the rapid ageing of highereducation teaching personnel; b) the outflow of young teachers to other sectors of employment; c) the reluctance of graduates of master programmes to build their career in the field of higher education; d) the lack of the general interest in postgraduate school as a traditional institute for the training of scientific and pedagogical personnel of the highest qualification in Russia; e) the reduced efficiency of the functioning of the institute of postgraduate education; f) the long period of becoming young teachers as candidates of science. The crisis is continuously increasing against the background of: a) the growth in the number of potential applicants – young people aged 18 to 24; b) the low income level of young university teachers, including most of the leading universities; c) the lack of the system of state support and stimulation of young teachers. There are currently no economic prerequisites for the use of “soviet” experience in terms of a significant increase in the financial attractiveness of postgraduate school and perspectives of scientific and pedagogical activities. Therefore, it is necessary to propose the measures at the federal level, taking into account modern realities. To resolve the problem mentioned above, the author’s concept of the state programme “Future Associate Professors” is proposed, which should be realised by organising two promotion trajectories: a) “student → assistant and postgraduate student → preparation and dissertation defence → associate professor”; b) “a practicing specialist with experience in the department’s profile → teacher and postgraduate student → preparation and dissertation defence → associate professor”. The innovations designed to ensure successful implementation of the programme are formulated and justified: a) state subsidies for a part of the cost of students’ and young specialists’ participation in the programme; b) targeted “teaching” budget places for postgraduate studies; c) the introduction of an additional criterion for evaluating universities in the framework of annual monitoring.Practical significance. The research results and proposals can be used by the Ministry of Education and Science of Russia, as well as by the heads of Russian universities to increase the effectiveness of their activities at the national and local levels.